2000
DOI: 10.1073/pnas.100108697
|View full text |Cite
|
Sign up to set email alerts
|

Steroid hormones induce HMG1 overexpression and sensitize breast cancer cells to cisplatin and carboplatin

Abstract: Cisplatin is an anticancer drug that has enjoyed remarkable success against testicular tumors, but dose limiting side-effects have limited its application against a broader range of cancers. Previous studies have shown that high-mobility group (HMG) domain proteins such as HMG1 sensitize cells to cisplatin by shielding its major DNA adducts from nucleotide excision repair. Estrogen treatment increases HMG1 mRNA levels in breast cancer MCF-7 cells. Herein, we describe that treatment of human cancer cells having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
157
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(162 citation statements)
references
References 49 publications
4
157
0
1
Order By: Relevance
“…Given the abundance of HMGB1 in nuclei, one copy per kb of the human genome, and its roles in various biological processes, it was hypothesized that the cellular HMGB1 level might modulate the cisplatin sensitivity of cancer cells. Consistent with this notion, hormone-induced HMGB1 up-regulation in MCF-7 breast cancer cells correlates with enhanced cisplatin sensitivity (27). Increased cisplatin sensitivity was also observed in a lung adenocarcinoma cell line transfected with a plasmid expressing HMGB2, a protein with more than 80% identity to HMGB1 (28).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Given the abundance of HMGB1 in nuclei, one copy per kb of the human genome, and its roles in various biological processes, it was hypothesized that the cellular HMGB1 level might modulate the cisplatin sensitivity of cancer cells. Consistent with this notion, hormone-induced HMGB1 up-regulation in MCF-7 breast cancer cells correlates with enhanced cisplatin sensitivity (27). Increased cisplatin sensitivity was also observed in a lung adenocarcinoma cell line transfected with a plasmid expressing HMGB2, a protein with more than 80% identity to HMGB1 (28).…”
supporting
confidence: 59%
“…There are, however, a number of scenarios that might prevent HMGB1 from interacting with cisplatin-modified DNA in the cells and modulating their responses to cisplatin. One possibility is that the HMGB1 level in the mouse embryonic fibroblasts is considerably lower than that of cells in other tissues or animals, such as MCF-7 human breast cancer cells, the subject of a previous study (27). A Western analysis for HMGB1 levels in both cell lines excluded this possibility.…”
Section: Resultsmentioning
confidence: 95%
“…Cisplatin-modified DNA can divert TBP from its natural binding site, the TATA box, thus inhibiting transcription initiation (13). When binding to platinum-DNA adducts, HMGB1 can interfere with repair of the damaged DNA (11,19). HMGB1 contains two HMG box domains (HMGB1a and HMGB1b), 80-amino acid DNA-binding motifs that recognize bent DNA structures (20,21).…”
Section: Cis-ddp Cis-diamminedichloroplatinum(ii) (Cisplatin)mentioning
confidence: 99%
“…He et al (42) reported an estrogen-induced increase in the transcription of HMGB1 in breast cancer cells. This observation suggested that endometrial HMGB1 expression, and possibly secretion, is steroid-dependent.…”
Section: Discussionmentioning
confidence: 99%